Proceso de nixtamalización de maíz (Zea mays L.), amaranto INIAP Alegría (Amaranthus caudatus L.) y quinua INIAP Tunkahuan (Chenopodium quinoa Willd.) a tres concentraciones y dos conservantes (benzoato de sodio - propionato de calcio) en los Laboratorios Académicos de la Carrera de Ingeniería Agroindustrial de la Universidad Técnica de Cotopaxi en el período 2015 – 2016. - Vásconez Albán, Jenny Elizabeth (2016)
In the process of nixtamalization of maize (Zea mays L.), amaranth INIAP Alegria (Amaranthus caudatus L.) and quinoa INIAP Tunkahuan (Chenopodium quinoa Willd.) at three concentrations and two preservatives (sodium benzoate - calcium propionate) were performed the following processes: reception of raw material, heavy, nixtamalized for 40-45 minutes to boiling, rest in the same cooking pot for 14 hours, washing 3-4 times, dehydrated, ground, heavy final flour. The process of chewing with the nixtamalized maize, quinoa and amaranth flour was as follows: reception of raw material, dosing, kneading, rest, molding, cooking, cooling, weighing of samples and storage. The chebolite was subjected to organoleptic evaluation where the factors to be evaluated were the color, smell, taste and acceptability evidenced by the three best treatments, which were t4 (30% quinoa + 30% amaranth + 70% corn + sodium benzoate) t5 (20% quinoa + 10% amaranth + 7% corn + sodium benzoate), t6 (20% quinoa + 10% amaranth + 70% corn + calcium propionate). Since the t6 treatment excelled among the three best treatments, the following nutritional content was described: protein 5.41%, total carbohydrates 37.8%, fat 6.43%, total dietary fiber 0.47%, vitamin A 34.9 IU/100g, vitamin C 2.17 mg/100g, the physicochemical and microbiological characteristics are detailed as follows: ash 1.40%, humidity 48.5%, pH 7.29%. Acidity is 0.054 mg / 100. Molds, yeasts, and E. coli were also determined, which do not exceed the permitted limits in established standards, demonstrating that the product poses no health risk. Thus, the cost of production of the treatment was set at 1.73 cents for a quantity of 200 g, due to high costs of raw materials.